2011
DOI: 10.1007/s10620-011-1765-0
|View full text |Cite
|
Sign up to set email alerts
|

Peginterferon Alfa-2a Is Superior to Peginterferon Alfa-2b in the Treatment of Naïve Patients with Hepatitis C Virus Infection: Meta-Analysis of Randomized Controlled Trials

Abstract: PEGIFN alfa-2a has superior efficacy with higher SVR as compared to PEGIFN alfa-2b in treatment-naïve HCV-infected patients. The safety profile of the two types of PEGIFN was similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
13
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 20 publications
6
13
0
1
Order By: Relevance
“…In contrast to prior clinical studies, this investigation reflected the treatment period and the patient age range present in real-world settings, and we included previously treated patients. 6,7,12,13) Ours is the first study focusing on the safety profiles of PEG-IFNs in a patient population with the variety of characteristics seen in actual clinical practice. As we have demonstrated that there is no significant difference in the safety profile of the two types of PEG-IFN when used in clinical practice, physicians can select the treatment regimen based on the predicted efficacy for each patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to prior clinical studies, this investigation reflected the treatment period and the patient age range present in real-world settings, and we included previously treated patients. 6,7,12,13) Ours is the first study focusing on the safety profiles of PEG-IFNs in a patient population with the variety of characteristics seen in actual clinical practice. As we have demonstrated that there is no significant difference in the safety profile of the two types of PEG-IFN when used in clinical practice, physicians can select the treatment regimen based on the predicted efficacy for each patient.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Studies investigating differences in adverse events between PEG-IFN α-2a combined with ribavirin and PEG-IFN α-2b combined with ribavirin, including the safety outcomes of randomized clinical trials in Japan and other countries, as well as the pooled analysis of these studies, have suggested that there are no or few differences between the two treatments. 6,7,12,13) However, these studies were conducted in clinical trial settings, and until now there have been no studies carried out in Japan using a nationwide database compiled from real world settings. 14) In addition, most of the previous studies did not consider confounding variables and time to withdrawal from treatment due to adverse events in their analyses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While the reduced clearance of PEG IFN-α 2a, provides measurable therapeutic plasma levels even at the end of the weekly dosing period (28). These differences between the two types of PEG IFNs provide better compliance and more safety of PEG IFN-α 2a (29).…”
Section: Discussionmentioning
confidence: 99%
“…Значимость этого показателя определяется увеличением ве-роятности наступления рецидива после курса противовирусной терапии по мере прогрессиро-вания заболевания печени [16]. Этим обусловле-на бóльшая длительность терапии и отсутствие возможности редуцирования курса противови-русной терапии у пациентов с выраженным фи-брозом или циррозом печени вне зависимости от наличия других благоприятных предикторов излечения.…”
Section: заключениеunclassified